Improving Quality Learning Subject Building Materials Science through Research Based Learning - Sumarni, Sri; Sunarsih, Ernawati Sri (Proceeding of International Conference on Teacher Training and Education, 2016)
Research based learning is a learning method that uses authentic learning, problem solving, cooperative learning, contextual, and the inquiry discovery approach. That is based on the philosophy of constructivism, to develop self-sustained and sustainable student. The purpose of research based learning is to create a learning process with analysisâs activity, synthesis, and evaluation also to improve the student and lecture about assimilation and application of knowledge also increases the capabilities of student as researcher. Itâs make the subject building material science more significance. The purpose of the research is to improve the quality of the student subject building material science based on research, the method of research used quantitative research. Samples were selected 34 students. The results showed that the first phase gets 200.3 score, then the second phase gets 209.24 of score, based on the observation concluded that using research based learning improve the quality of learners.